Er:YAG Laser Cleaning of Painted Surfaces: Functional Considerations to Improve Efficacy and Reduce Side Effects - Cong Wang (MDPI AG, 2021)
The restoration of paintings always involves the removal of darkened superficial layers, which are mainly due to dust deposition and aged varnishes. As cleaning is an irreversible and invasive treatment, physical methods (i.e., laser cleaning) instead of chemical ones are frequently suggested to reduce side effects on pictorial layers. Among the most employed laser systems, the free-running Er:YAG laser is considered very suitable for fine arts cleaning. This laser works at 2.94 μm, at which only –OH and –NH bonds in molecules are excited. This character can become a disadvantage when pigments with these functional groups are present. To understand the potential of the Er:YAG laser in such situations or in the presence of degradable pigments, the effectiveness of varnish removal from paintings prepared with egg yolk as the binder and cinnabar and lead white as the pigments were systematically investigated. Different cleaning conditions were used, and a hyperspectral sensor was innovatively used as a rapid, in situ and non-destructive technique to assess the effects of laser ablation, besides microscopic analysis. Though results obtained show all these pigments are sensitive to this laser radiation, satisfactory cleaning can be achieved without damaging the pictorial layer. The best cleaning conditions were 0.5 W of power (50 mJ and 10 Hz for energy and frequency), with 2-propanol as the wetting agent.